Thermodynamic analysis of a thermoelectric air conditioner - Chanchira Channoy; Somchai Maneewan; Chantana Punlek (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper discusses the results of tests done to investigate the performance of a thermoelectric air conditioner (TEAC). The TEAC is composed of twelve thermoelectric modules (TEMs). The TEMs were fixed to rectangular fin heat sinks on both their hot and cold sides. With an increased input voltage, the cooling capacity increased. At a 6 V input voltage flow, a suitable condition occurred. The rate of hot air flow was 0.48 kg/min, and the cooling capacity was 157.0 W, resulting in an outlet air temperature of 28 oC. The coefficient of performance (COP) was calculated and found to be 0.92. Exergy analysis is used to determine the energy flows and second law efficiencies of a TEMs system and its components. The exergy destruction and second law efficiency were observed to increase when the TEAC's input voltage was increased. The TEAC's maximum exergy efficiency was 0.35, which was low compared to the coefficient of performance.